Darkness color index analysis using android-based RGB colorimeter for educational science purposes - Maulana Ashidiq, Rizki; Cahya Prima, Eka; Riandi (Insitut Pendidikan Indonesia, 2023)
The UNESCO outlined eight essential competencies that crucial for students to attain the 21st demands. Engaging science learning activities through the experimental practicum can empowers students to employ critical, active, and collaborative thinking when addressing scientific challenges, particularly those related to environmental pollution. The objective of this study how does the effect of TAR amount towards darkness color index using RGB colorimeter application. The research methodology in this study is science practicum development. In this study, science practicum activities are combined with STEM and Project-Based Learning model in conducting the activities. After conducting the experiment, the result shows that the quality of color residue is depend on the amount of TAR and Nicotine inside tobaccos. More amount of TAR in Tobaccos is Darker the color of residue. Furthermore, there are lots of variables that we should consider in this experiment. For example, duration of tobacco smoking (time), the volume of water inside the plastic bottle (volume), and the length of tobaccos (length). Because the variables can affect the tobacco residue and affect the RGB color index.